Potensi Pajak Dan Retribusi Parkir Di Kota Kendari (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
This study aims to determine the potential for parking taxes and levies in the city of Kendari. The research method used is descriptive method with content analysis or content analysis. Broadly speaking, this writing systematic is more of a narrative nature which collects secondary data from BPS, opinions of experts, journals, books and articles published on the internet related to potential taxes and parking levies in the city of Kendari. The results showed that the revenue from parking, both in the form of taxes and levies, was still very low, although mathematically there was a huge potential for revenue from this sector. The implication of this is that the government must be fast in building its supporting infrastructure so that it can collect taxes and parking fees to the maximum and there is no more illegal parking which sometimes disturbs the public and reduces local revenue.